Optimization of The Role of FKUB And Kesbangpol Role (Nation and Political Unity) in Handling The Radical Movement of Terrorism in Tasikmalaya District - Rahmat, Rahmat; Bestari, Prayoga; Nurdin, Encep Syarief; Tanshzil, Sri Wahyuni (Universitas Pendidikan Indonesia, 2020)
This study illustrates the synergy between the Forum for Religious Harmony (FKUB) with the National Unity and Politics (Kesbangpol) in dealing with the radical terrorism movement in Tasikmalaya Regency. Some efforts to handle religious conflicts that lead to radicalism movement include mapping conflict-prone areas, the formation of the Regional Intelligence Community (Kominda) and the Integrated Team for Handling Social Conflicts by the National Unity and Politics and the establishment of the Rukun Living Movement Task Force (SGHR) at the sub-district level by FKUB as a collaborative strategy step handling religious conflicts in Tasikmalaya Regency. The purpose of this study is to determine the role of FKUB as well as the synergy established between local governments, terrorism management institutions and the community in efforts to tackle radical terrorism. The method used in this study is a qualitative approach that emphasizes data collection through interviews, observations, documentation and focused discussions (Focus Group Discussion).